PHENOMENA AND HISTORY OF ISLAMIC POLITICAL PARTIES IN INDONESIA - Yulianti, Nanik (Universitas Islam Negeri Raden Intan Lampung, 2015)
Politics, coming back to its original meaning which might be defined as influencing other people and which is involves the making of a common decision for people, then, life is never politics-free. When we are thinking, we are contributing in the political life, how to influence or how to be influenced, how to make a decision in life or how to follow a decision. Politics contain of many dimensions, one might think politics in a negative or positive way depending on which dimensions he stick the politics with. Political party is one of the main institutions in the political life which used in practicing the democracy as the representative system needed by the community. It used as a media to transfer the political messages from the community to the government, as peoples’ media to send their aspiration to the people ‘above’, which existence is influencing the development of the policies of the country depending on its effectiveness. As a Muslim-Largest country, Islam has a very important role in Indonesia’s political zone. Though, not everything that has an “Islam” name is able to completely represent Islamic values and so some “non-Islam” might also represent Islamic ethical values. The point of this article is to focus more on how is the relationship between politics and Islam in Indonesia by observing the development of Islamic Political Parties and its phenomena. It will be well observed by the historic-phenomenology approach, which is describing and observing the history of Islamic Political Parties in Indonesia and the social facts that happened in the society